2019
DOI: 10.1111/eea.12735
|View full text |Cite
|
Sign up to set email alerts
|

Host plant or geographic barrier? Reproductive compatibility among Diatraea saccharalis populations from different host plant species and locations in Argentina

Abstract: The sugarcane borer, Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae), is one of the main lepidopteran pests of sugarcane and maize. The association of insects with different environments and/or host plants may occur by adaptation and this can generate host races. Adaptation may produce phenotypic or genotypic variation, which results in the differences in bioecological characteristics such as reproductive compatibility that reduces gene flow among populations. The objective of this study was to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
(101 reference statements)
0
5
2
Order By: Relevance
“…In a study of the plant pathogenic fungus Calonectria morganii Crous et al, the genetic diversity among progeny was remarkable when compared to the field isolates, which were much less variable, revealing that sexual reproduction has hardly occurred in the isolated strains (Overmeyer et al, 1996). In the present study, more different haplotypes were detected in field‐collected samples, and those found in the offspring did not add relevant information related to the low fitness previously found (Fogliata et al, 2019).…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…In a study of the plant pathogenic fungus Calonectria morganii Crous et al, the genetic diversity among progeny was remarkable when compared to the field isolates, which were much less variable, revealing that sexual reproduction has hardly occurred in the isolated strains (Overmeyer et al, 1996). In the present study, more different haplotypes were detected in field‐collected samples, and those found in the offspring did not add relevant information related to the low fitness previously found (Fogliata et al, 2019).…”
Section: Discussioncontrasting
confidence: 70%
“…DNA was extracted from a total of 288 insects -175 from field collections and 113 from offspring obtained from the cross experiments made by Fogliata et al (2016Fogliata et al ( , 2019 -among individuals of different regions and host plants. Analyses were performed on 102 sequences (35 of insects from five pure populations and 67 from offspring) selected from a total of 288 sequences, considering their length and the quality of the nucleotides.…”
Section: Mitochondrial Coi Variationmentioning
confidence: 99%
See 2 more Smart Citations
“…Entomologia Experimentalis et Applicata has a long history in publishing studies on host race formation and speciation. The number of articles on this topic exceeds 300 over the period 1968-2021 including seminal reviews by Feder & Filchak (1999) and Matsubayashi et al (2010) as well as several case studies in the last few years (e.g., Saint Jean et al, 2018;Tadeo et al, 2018;Fogliata et al, 2019;Hensen et al, 2020). It becomes clear from these publications that many questions remain concerning host race formation.…”
Section: Introductionmentioning
confidence: 99%